PENGARUH EARNINGS MANAGEMENT TERHADAP FUTURE PROFITABILITY TERKAIT DENGAN OWNERSHIP STRUCTURE, FIRM SIZE DAN CORPORATE GOVERNANCE PRACTICES - Ikhsan Yudha Asmara; Felizia Arni Rudiawarni (Media Ekonomi, 2012)
This study aims to determine how the effect of earnings management on future profitability business entity engaged in the manufacturing sector listed on the Indonesia Stock Exchange, and how the effects of the ownership structure, company size, and the practice of corporate governance (proxied by the audit quality, independent board member and audit committee) regarding the impact of earnings management on the future profitability of manufacturing sector enterprises listed on the Stock Exchange. This study used a sample of manufacturing sector companies listed on the Indonesia Stock Exchange in the period 2008-2010. The samples used in this study were 262 observations. The sampling method used was probability sampling - judgment / purposive sampling. Independent variables used in this study are earnings management (proxied by the CFO, NDAC, and DAC), ownership structure (proxied by DFAM and INST), firmsize, and corporate governance practices (proxied by the AUDIT, BOD, and AUDCOM). The dependent variable in this study is the future profitability proxied by the variable "and CFOT earnt + 1 + 1. The results of this study were (1) earnings management proved to have a significant impact on the future profitability of manufacturing sector enterprises. The influence that appears different depending on the proxy used; (2) The ownership structure did not have an influence on the behavior of earnings management related to future profitability of manufacturing sector enterprises; (3) firmsize not affect earnings management behaviors related to future profitability of manufacturing sector enterprises; overall corporate governance practices are not effective in influencing the behavior of earnings management related to the future profitability of manufacturing sector enterprises. Keywords  :   future profitability, earnings management, ownership structure, corporate governance practice